ClinicaVR: Classroom-CPT: A virtual reality tool for assessing attention and inhibition in children and adolescents. (June 2016) - Nolin, Pierre; Stipanicic, Annie; Henry, Mylène; Lachapelle, Yves; Lussier-Desrochers, Dany; Rizzo, Albert "Skip"; Allain, Philippe
Abstract: Having garnered interest both in clinic and research areas, the Virtual Classroom (Rizzo et al., 2000) assesses children's attention in a virtual context. The Digital MediaWorks team (www.dmw.ca ) has evolved the original basic classroom concept over a number of iterations to form the ClinicaVR Suite containing the Classroom-CPT as one of its components. The present study has three aims: investigate certain validity and reliability aspects of the tool; examine the relationship between performance in the virtual test and the attendant sense of presence and cybersickness experienced by participants; assess potential effects of gender and age on performance in the test. The study was conducted with 102 children and adolescents from Grade 2 to Grade 10. All participants were enrolled in a regular school program. Results support both concurrent and construct validity as well as temporal stability of ClinicaVR: Classroom-Continuous Performance Test (CPT). Gender exerted no effect on performance, while age did. The test did not cause much cybersickness. We recommend ClinicaVR: Classroom-CPT as an assessment tool for selective and sustained attention, and inhibition, in clinic and research domains. Highlights: This study support the validity and temporal stability of ClinicaVR: Classroom-CPT. The ClinicaVR: Classroom-CPT improves the neuropsychological assessment from an ecological perspective. The ClinicaVR: Classroom-CPT is recommended to evaluate attention and inhibition deficits in children and adolescents.